Effect of Saffron Extract on Pituitary-Testis Axis in Mice - Nazem, Habibollah; Modaresi, Mehrdad; Messripour, Manochehr; Asadi Marghmaleki, Mehran; Ghaffar Ebadi, Abdol (Asian Journal of Chemistry, 2010)
The object of the present study is to assess the efficacy of C. sativus in the hormone changes in pituitary-testis axis of mice. Four group including eight adult male Balb/C mice weighing 30 ± 5 g were used in this study. Normal saline administered as placebo to control group and saffron extract in doses of 25, 50 and 100 mg/kg/48 h were injected intraperitoneally for 20 d to experimental groups. FSH, LH and testosterone in serum samples, were measured by ELISA.In comparison with plasebo the level of FSH, LH and testosterone significantly increased in 100 mg/kg saffron treated group, but no significant differences were observed between other treatments and placebo. The results of this study indicate the efficacy of saffron extract in the male reproductive endocrine function and showed that it can modify the reproduction activities.